2021
DOI: 10.3389/fonc.2021.655093
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the Extraprostatic Extension Grade on MRI and Its Incremental Value to Clinical Models for Assessing Extraprostatic Cancer

Abstract: ObjectivesTo externally validate the extraprostatic extension (EPE) grade criteria on MRI and analyze the incremental value of EPE grade to clinical models of prostate cancer.MethodsA consecutive 130 patients who underwent preoperative prostate MRI followed by radical prostatectomy between January 2015 to January 2020 in our institution were retrospectively enrolled. The EPE grade, Cancer of the Prostate Risk Assessment (CAPRA), and Memorial Sloan Kettering Cancer Center nomogram (MSKCCn) score for each patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Subsequently, some scholars conducted external verification on the prediction of pathological EPE by EPE grade. Among them, Xu et al [ 13 ] conducted external validation of EPE grade results, showing that EPE grade has high accuracy in predicting pathological EPE, and the sensitivity is significantly improved (sensitivity 0.767-0.778). There is a meta-analysis of EPE grade predicting pathological EPE [ 14 ], which included 4 studies and 1294 patients, and results showed that the EPE grade system showed high sensitivity (82%) and medium specificity (63%), with an AUC of 0.82 (95% CI 0.79–0.85).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, some scholars conducted external verification on the prediction of pathological EPE by EPE grade. Among them, Xu et al [ 13 ] conducted external validation of EPE grade results, showing that EPE grade has high accuracy in predicting pathological EPE, and the sensitivity is significantly improved (sensitivity 0.767-0.778). There is a meta-analysis of EPE grade predicting pathological EPE [ 14 ], which included 4 studies and 1294 patients, and results showed that the EPE grade system showed high sensitivity (82%) and medium specificity (63%), with an AUC of 0.82 (95% CI 0.79–0.85).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 29 studies were excluded due to insufficient data to reconstruct 2 × 2 tables, not in the field of interest, and could not reproduce the sensitivity and specificity. Consequently, a total of 4 studies comprising 1,294 participants were included in the present meta-analysis (18,(25)(26)(27).…”
Section: Literature Search and Data Extractionmentioning
confidence: 99%
“…In all studies, the MRI images were interpreted by 2 radiologists independently with experience of 2-15 years. The inter-reader agreement calculated with kappa values was reported by 3 studies, which ranged from 0.47 to 0.88 (25)(26)(27). In 1 study, the MRI was performed with a 1.5-T scanner (25), whereas all the remaining 3 studies used 3.0-T scanners.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations